Model Desain Sistem Informasi Pengembangan Pemasaran Hewan Qurban Berbasis Web - Magdalena, Hilyah; Septryanti, Ade; Cillia, Cillia (METIK JURNAL (AKREDITASI SINTA 3), 2023)
In Pangkalpinang City and its surroundings, people who need sacrificial animals only look for them in their area. However, currently marketing sacrificial animals can also use a web-based system. CV. Ternak Sejahtera developed its marketing system with a web system to reach customers outside Pangkalpinang. The development of this marketing system was carried out using the Rapid Application Development method which is able to accommodate user needs well and repeat the system analysis and design process if there are changes to system requirements. This web-based system is designed so that customers can view sacrificial animals and make transactions online. The system also provides installment payment facilities for customers who purchased long ago. Customers also receive a service to deliver sacrificial animals with the guarantee that the animals are in good health and meet the requirements for sacrificial animals.